A decision consequence-based model to understand the phenomena in motorcycle engineering design from a human factor's perspective. (24th February 2021) - Agius, Sean; Farrugia, Philip; Francalanza, Emmanuel
Research has shown that motorcycle riders' persona and posture have a large impact on motorcycle safety, bringing these challenges into the domain of human factors. Besides these aspects, motorcycle designers must consider the emotional values of such artefacts for it to be successful in the market. Indeed, motorcycle designers must take into account multitude of factors when developing such artefacts. These all pose challenges to designers whilst carrying out motorcycle design. A study was carried out with motorcycle designers to investigate their current design practices, and challenges faced during motorcycle design. A critical literature review revealed that there is a research gap in decision consequence models which do not take a holistic view of the underlying phenomena during design decision-making of motorcycle designers. The gap in literature together with the outcome of the study, collectively led to the development of a decision consequence-based phenomena model during motorcycle design. The model is validated with two case studies from the motorcycle industry through the use of a comparative-validation approach.